Socio-Economic Conditions of Communities Working in the Informal Sector in Cipadung Village - Sopyan; Muizzul Fadhillah; ⁠Muhammad Bushiri; Sri Damayanti (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
This study aims to analyze the socioeconomic conditions of people working in the informal sector in Cipadung Village. The informal sector plays a crucial role in absorbing labor, especially those without access to formal employment. However, this sector also faces various challenges related to income instability, limited access to capital, and minimal social protection. This study employed a qualitative approach with library research, where data was drawn from various secondary sources such as books, scientific journals, and reports from official institutions such as the Central Bureau of Statistics, the International Labour Organization, and the World Bank. Data analysis was conducted through content analysis to identify patterns and relationships between relevant concepts. The results indicate that the economic conditions of people in the informal sector tend to be vulnerable, characterized by low and unstable incomes and limited access to economic resources. Socially, people in the informal sector generally have low levels of education and limited access to health and education services, despite having strong social ties within their communities. Furthermore, people's socioeconomic conditions are influenced by various factors, such as education level, access to capital, social environment, and government policies. Thus, comprehensive efforts are needed through inclusive policies and empowerment of people to improve the welfare of informal sector workers in a sustainable manner.